Digitalizing land administration: The geographies and temporalities of infrastructural promise. Issue 122 (June 2021) - Rodima-Taylor, Daivi
Highlights: Blockchain technology is increasingly explored for advancing transparent land administration. Blockchain-based land registries are embedded also in non-digital and human infrastructures and legacies of colonial extraction. Blockchain registries may obscure the complex layering of formal and informal claims to land in the Global South. They may advance an unrealistic expectation of changing property relations through technical means. The aspirational promise of the technology varies geographically and is central to its public legitimation. Abstract: Blockchain technology has been explored recently for digitalizing land administration in different parts of the world. It has been viewed as contributing to formalization of property rights in the Global South, and enhancing coordination of real estate markets in the Global North. Suggesting that blockchain applications may entail an unrealistic promise of effecting change in property relations through technical means, the article explores the integration of blockchain with existing modes of land administration in three countries – Ghana, Georgia, and Sweden. It investigates the broader embeddedness of blockchain-based land registries in non-digital infrastructural modalities and the peopled infrastructures of informal networks. It argues that the abstraction of blockchain may obscure the complex layering of formal and informal, institutionalized and grassroots texture of property rights and claims to land. Investigating the "infrastructural promise" of blockchain through narratives advanced around this novel "automated trust" mechanism, the article explores the potential of blockchain land registries to perpetuate territories of dispossession grounded in colonial legacies and present-day inequalities.